The article examines the concept of local self-government in the Constitution of Ukraine - Хорт, Ігор Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The author draws attention to local self-government as the basic principle of the constitutional order of Ukraine - one of the most important principles of organization and functioning of public power in society and state.